Analyzing the behavior toward Tempeh waste management at the home-scale industry level in Tempeh Village Sukomanunggal Surabaya - Hardian Eko Nurseto; Muhammad Ainul Fahmi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Tempeh is a daily food, especially for Indonesians. Many people consume it as a source of protein for their staple food. However, people rarely know how Tempeh is produced in Indonesia. Most Tempeh is made by  the home-scale industry, which still lacks in environmental awareness. Therefore, many Tempeh industries still directly dispose of their waste, causing environmental pollution in neighborhood areas. This study aimed to analyze the behaviors of the owners of the Tempeh industry concerning waste disposal or treatment.  The respondents in this study were the owners of the home-scale Tempeh industry located in  Tempeh Village Sukomanunggal Surabaya City. The collected data were processed using the structural equation model partial least square (SEM PLS) to determine the factors influencing  the behavior toward waste disposal or waste treatment. The results showed various factors affecting the owners in disposing or treating waste from Tempeh production. These were Attitude Toward Behavior (ATB), Subjective Norm (SN), Perceived Behavioral Control (PBC), Environmental Awareness (EA), Government Intervention (GI), and Knowledge (KN), which affect the Intention to Manage Tempeh Waste Generation (IMTWP). The findings confirmed that the goal to treat Tempeh waste enhances the owners’ behaviors to manage the disposal or treatment of the waste from  Tempeh Village in Sukomanunggal - Surabaya.